Effects of prostaglandin E2 on disease activity, gastric secretion and intestinal permeability, and morphology in patients with rheumatoid arthritis. Issue 8 (August 1988) - Henriksson, A E; Tagesson, C; Uribe, A; Uvnäs-Moberg, K; Nord, C E; Gullberg, R; Johansson, C
Abstract : The effects of oral natural prostaglandin E2 (PGE2) on symptoms, disease activity, and gastrointestinal functions in rheumatoid arthritis (RA) were studied in an open pilot trial. Twelve patients, six taking and six not taking non-steroidal anti-inflammatory drugs (NSAIDs), received 1 mg natural PGE2 three times a day for six weeks. The treatment was tolerated well and the only side effect noted was slightly looser stools in three patients. Half of the patients reported subjective improvement and none had aggravation of symptoms. The Ritchie articular index and several biochemical inflammation markers decreased and were significantly reduced at the end of the treatment period. The thickness of the small intestinal mucosa increased during the PGE2 treatment. The intestinal permeability pattern, measured by urinary excretion of polyethylene glycols (PEG 400), differed between the patients taking and not taking NSAIDs. The initially high urinary PEG 400 excretion values in the patients taking NSAIDs decreased and the initially low excretion values in patients not taking NSAIDs increased during the PGE2 treatment. The jejunal contents became sterile in 5/6 patients not taking NSAIDs and remained sterile in 1/6 patients taking NSAIDs at the end of the treatment. The treatment period was associated with a reduction of lactobacilli in patients not treated with NSAIDs. Thus the treatment appeared to decrease disease activity and to improve small intestinal functions in patients with RA, findings that need confirmation in a controlled trial.